Contrasting Trends in Abundance of Indian Vultures (Gyps indicus) Between Two Study Sites in Neighboring Indian States - McClure, Christopher J. W.; Rolek, Brian W.; Virani, Munir Z. (Frontiers in Ecology and Evolution, 2021)
Indian Vultures (Gyps indicus) are critically endangered, yet are poorly monitored. We analyze counts of breeding pairs of Indian Vultures in Central India, specifically the eastern portions of the Indian states of Rajasthan and Madhya Pradesh over a period of 10 years and reveal the populations were on differing trajectories from 2007–2016. Indeed, the difference between population levels of the study areas nearly doubled during our study, with the population in Rajasthan falling relative to Madhya Pradesh. Future research should examine potential drivers of population declines and establish a long-term monitoring program that informs current conservation strategies for Indian and other vultures across their range.